The impact of stroke subtype on recovery and functional outcome after inpatient rehabilitation: a retrospective analysis of factors - Krishnan, Rathi Ratha (2023)
The aims of this study were to compare inpatient rehabilitation outcomes between acute stroke subtypes of Cerebral Infarction (CI) and Intracerebral Hemorrhage (ICH), and to determine the predictors of discharge outcomes. A retrospective study of stroke inpatients was carried out using the discharge Functional Independence Measure (FIM) as the primary outcome measure. Relationships between stroke subtype, rehabilitation impairments, and medical complications on FIM -gain were analyzed. Altogether, 280 datasets including 211 (75.4%) CI and 69 (24.6%) ICH were analyzed. ICH patients were significantly younger than CI patients (55 years ICH vs. 64.0 years CI years, p < 0.001), had a 10-fold higher proportion needing ICU admission (ICH 82.6% vs. CI 7.6%, p < 0.001), and had significantly lower total admission FIM scores (67 points ICH vs. 74 CI points, p = 0.006), with lower motor-FIM scores in particular (38 points ICH vs. 48 points CI, p = 0.003). Significant functional improvements after inpatient rehabilitation, i.e., FIM gain, occurred regardless of stroke subtype (FIM-ICH Δ 27 vs. FIM-CI Δ 21, p = 0.05). Despite significantly worse initial stroke severity, ICH patients achieved similar functional gains, independence levels, and return-home rates compared with their CI counterparts after inpatient rehabilitation.